2014
DOI: 10.1371/journal.pone.0089979
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Upregulation of Endogenous VEGF-A Reduces Myocardial Infarct Size in Mice

Abstract: “Epigenetherapy” alters epigenetic status of the targeted chromatin and modifies expression of the endogenous therapeutic gene. In this study we used lentiviral in vivo delivery of small hairpin RNA (shRNA) into hearts in a murine infarction model. shRNA complementary to the promoter of vascular endothelial growth factor (VEGF-A) was able to upregulate endogenous VEGF-A expression. Histological and multiphoton microscope analysis confirmed the therapeutic effect in the transduced hearts. Magnetic resonance ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 22 publications
(33 reference statements)
2
33
0
Order By: Relevance
“…tiviral shRNAs used (negative LV-856 or positive LV-451) persistent epigenetic changes occur on the VEGF promoter, including modifications in histone H3K9 methylation and acetylation. In a later report, these shRNAs were successfully applied in an acute therapeutic intervention in a myocardial infarction mice model (31). The identification of such in vivo repressor or inducer of VEGF expression is an obligatory step for future clinical studies.…”
Section: Figmentioning
confidence: 99%
“…tiviral shRNAs used (negative LV-856 or positive LV-451) persistent epigenetic changes occur on the VEGF promoter, including modifications in histone H3K9 methylation and acetylation. In a later report, these shRNAs were successfully applied in an acute therapeutic intervention in a myocardial infarction mice model (31). The identification of such in vivo repressor or inducer of VEGF expression is an obligatory step for future clinical studies.…”
Section: Figmentioning
confidence: 99%
“…The role of CREB2 in the regulation of VEGF-A is very interesting and warrants further studies. We have previously found H3K27 to be the most important histone residue for the epigenetic regulation of mouse VEGF-A expression [8,9]. Also, we have shown that CBP/CREB interaction inhibitor abolishes the shRNA-mediated upregulation of VEGF-A.…”
Section: Discussionmentioning
confidence: 79%
“…CREB, which binds to CRE [23], regulates the H3K27 acetylation by binding CREB binding protein (CBP)/p300 and CREB Regulated Transcription Coactivator (CRTC) [24]. When cells were treated with CBP-CREB interaction inhibitor, the shRNA-mediated VEGF-A upregulation was reduced to the level of shRNA control [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When we delivered these shRNAs to ischemic mouse hindlimbs in vivo using lentiviral vectors, we observed increased vascularity in muscles where expression of Vascular Endothelial Growth Factor A (VEGF-A) was upregulated by TGA [6]. In a later study, we analyzed therapeutic potential of shRNA mediated TGA of VEGF-A in a murine myocardial infarction model [7]. In the treated group infarction size was siqnificantly reduced after two weeks of lentiviral injection as analyzed by MRI and histology.…”
Section: Descriptionmentioning
confidence: 99%